2020
DOI: 10.1002/jmv.26736
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of antibody tests for detecting infant respiratory syncytial virus infection

Abstract: Respiratory syncytial virus (RSV) infection is a major cause of respiratory tract disease in young children and throughout life. Infant infection is also associated with later respiratory morbidity including asthma. With a prospective birth cohort study of RSV and asthma, we evaluated the performance of an RSV antibody enzyme‐linked immunoassay (EIA) for detecting prior infant RSV infection. Infant RSV infection was determined by biweekly respiratory illness surveillance plus RSV polymerase chain reaction (PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Twenty-seven studies [ 13–39 ] provided descriptive data on the clinical decisions to test for RSV in various settings: 16 provided data for IP [ 13–16 , 18–29 ], 1 for IP and for ED [ 17 ], 9 for ED [ 30–38 ], and 1 for OP [ 39 ] ( Supplementary Table 3 A and 3 B ). Thirteen studies describing laboratory testing practice for combined settings (ie, IP with other settings, ED with other settings, or OP with other settings) are listed in Supplementary Table 3 C .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-seven studies [ 13–39 ] provided descriptive data on the clinical decisions to test for RSV in various settings: 16 provided data for IP [ 13–16 , 18–29 ], 1 for IP and for ED [ 17 ], 9 for ED [ 30–38 ], and 1 for OP [ 39 ] ( Supplementary Table 3 A and 3 B ). Thirteen studies describing laboratory testing practice for combined settings (ie, IP with other settings, ED with other settings, or OP with other settings) are listed in Supplementary Table 3 C .…”
Section: Resultsmentioning
confidence: 99%
“…Six studies [ 39 , 42 , 56 , 62 , 69 , 70 ] reported RSV laboratory testing incidence proportions in the OP setting ( Figure 4 ; Supplementary Table 5 A ). The highest RSV laboratory testing incidence proportion was observed in 2 studies with LRTI infant populations [ 42 , 56 ].…”
Section: Resultsmentioning
confidence: 99%